2016
DOI: 10.1002/etc.3361
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of benzo[a]pyrene from microplastics to Artemia nauplii and further to zebrafish via a trophic food web experiment: CYP1A induction and visual tracking of persistent organic pollutants

Abstract: The uptake of microplastic particles and the transfer of potential harmful substances along with microplastics has been studied in a variety of organisms, especially invertebrates. However, the potential accumulation of very small microplastic particles along food webs ending with vertebrate models has not been investigated so far. Therefore, a simple artificial food chain with Artemia sp. nauplii and zebrafish (Danio rerio) was established to analyze the transfer of microplastic particles and associated persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
244
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(258 citation statements)
references
References 49 publications
6
244
0
8
Order By: Relevance
“…can ingest microplastic fibers. Prior work has demonstrated Artemia nauplii can ingest 1-5 µ m and 10-20 µ m fluorescent PE microbeads (1.2 × 10 6 microplastics per 20,000 nauplii), which were trophically transferred to predatory zebrafish (Danio rerio) 39 . In another study, consumption and adherence of 40 nm NH 2 and 50 nm COOH coated PS nanoparticles (5-100 µ g mL −1 ) resulted in impaired feeding, altered motility and increased molting in Artemia franciscana larvae 40 .…”
Section: Resultsmentioning
confidence: 99%
“…can ingest microplastic fibers. Prior work has demonstrated Artemia nauplii can ingest 1-5 µ m and 10-20 µ m fluorescent PE microbeads (1.2 × 10 6 microplastics per 20,000 nauplii), which were trophically transferred to predatory zebrafish (Danio rerio) 39 . In another study, consumption and adherence of 40 nm NH 2 and 50 nm COOH coated PS nanoparticles (5-100 µ g mL −1 ) resulted in impaired feeding, altered motility and increased molting in Artemia franciscana larvae 40 .…”
Section: Resultsmentioning
confidence: 99%
“…PEparticles provided by the same supplier have already been used in recent studies on effects of microplasics (e.g. Batel et al, 2016;Khan et al, 2015). Two different size classes were used for experiments (particles with 1e4 mm and 90e106 mm in diameter), hereafter referred to as 1-mm and 100-mm particles.…”
Section: Characteristics Of Particles and Their Behaviour In Aqueousmentioning
confidence: 99%
“…Perry et al (2013) found a "ball" of nylon fishing line in little auk that was inside the stomach of a fish. Trophic transfer of microplastics has been demonstrated experimentally in several species ranging from zooplankton to larger invertebrates to fish (Setälä et al, 2014;Farrell & Nelson, 2013;Batel et al, 2016).…”
Section: Ingestionmentioning
confidence: 99%